HIGHER EDUCATION QUALITY ASSURANCE: FINLAND'S EXPERIENCE - Svitlana Zaskaleta (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article discusses the main approaches to quality assurance in higher education in Finland. The relevance of studying the experience for Ukraine is determined. Quality assurance in higher education is governed by the legal framework of the country. External evaluation is carried out by the Finnish Education Evaluation Center (FINEEC). The objectives of the FINEEC are: evaluation of education, teaching, teachers and activities of higher education institutions; development of educational evaluation; evaluation of the results of training in basic education, higher secondary education and training, basic education in the arts. Finnish higher education institutions are primarily responsible for the quality of education. Self-esteem is accomplished through a digital platform. Program accreditation aims to increase international recognition. The author notes that Higher Education Institutions are actively involved in external evaluations. The quality assurance mechanism of education is constantly being improved. The results of the external evaluation are used as a benchmark for internal evaluation. Higher education institutions select a national or international team to audit. Particular attention is paid to the accreditation of programs. The analysis of the quality assurance system of higher education gives grounds to claim that it is an effective organization, which provides the necessary resources (academic and administrative staff, students, scientific and administrative leaders, financial, material, information, scientific, educational resources, etc.); effective activity of relevant bodies that ensure the quality of higher education of the country; designation of audit teams; identifying audit objectives; undergoing appropriate procedure; defining clear evaluation criteria that demonstrate the effectiveness and quality of the evaluation. The outlined approaches and methods of quality assurance of education serve as an example of imitation for quality assurance of higher education of Ukraine and a guideline for its development.